2023
DOI: 10.3389/fendo.2023.1287593
|View full text |Cite
|
Sign up to set email alerts
|

Risk factor analysis and prediction model for papillary thyroid carcinoma with lymph node metastasis

Juerong Lu,
Jintang Liao,
Yunhao Chen
et al.

Abstract: ObjectiveWe aimed to identify the clinical factors associated with lymph node metastasis (LNM) based on ultrasound characteristics and clinical data, and develop a nomogram for personalized clinical decision-making.MethodsA retrospective analysis was performed on 252 patients with papillary thyroid carcinoma (PTC). The patient’s information was subjected to univariate and multivariate logistic regression analyses to identify risk factors. A nomogram to predict LNM was established combining the risk factors. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Furthermore, previous studies ( 18 , 22 , 33 ) have identified several risk factors for cervical CLNM in PTC, such as microcalcifications, nodule size, and multifocality. Microcalcifications are an important ultrasonographic feature in the diagnosis of PTC.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, previous studies ( 18 , 22 , 33 ) have identified several risk factors for cervical CLNM in PTC, such as microcalcifications, nodule size, and multifocality. Microcalcifications are an important ultrasonographic feature in the diagnosis of PTC.…”
Section: Discussionmentioning
confidence: 97%